ANALISA KEBIJAKAN KETENAGAKERJAAN KOTA BEKASI - Andi Sopandi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2009)
Manpower planning is a systematic planning process is used as a basis and reference in formulating policies, strategies, and implementation of sustainable manpower development programs. Therefore, the required analysis of potential, input, process, output and employment in a comprehensive impact